The long‐term impacts of deer herbivory in determining temperate forest stand and canopy structural complexity. Issue 3 (20th December 2021) - Reed, Samuel P.; Royo, Alejandro A.; Fotis, Alexander T.; Knight, Kathleen S.; Flower, Charles E.; Curtis, Peter S.
Abstract: Ungulates place immense consumptive pressure on forest vegetation globally, leaving legacies of reduced biodiversity and simplified vegetative structure. However, what remains unresolved is whether browse‐induced changes occurring early in succession ultimately manifest themselves in the developed forest canopy. Understanding the development and persistence of these legacies is critical as canopy structure is an important determinant of forest ecosystem functions such as carbon sequestration and wildlife habitat. We measured how white‐tailed deer Odocoileus virginianus browse during stand initiation affected canopy structure, tree species richness, diversity, stem density, and basal area on Pennsylvania's Allegheny Plateau using a portable canopy LiDAR system. We capitalized on an historic deer enclosure experiment where forests were subjected to four deer densities (4, 8, 15, and 25 deer/km 2 ) for 10 years following stand initiation. Deer browsing impacts on the forest canopy are apparent nearly four decades since stand initiation. The highest deer density treatment experienced a significant reduction in tree species diversity, density, and basal area with stands becoming dominated by black cherry Prunus serotina . Reductions in overstorey diversity and tree density resulted in a more open canopy with low leaf area and high horizontal leaf variability. Canopies were tallest at the lowest and highest deer densities. Synthesis and applications . Using a portable canopy LiDAR system and a former deer enclosure experiment, we show that high deer browsing pressure during stand initiation can have a decades‐long impact on stand and canopy structure. High deer densities led to stands with lower species diversity and tree density, which resulted in canopies that were taller and less dense. As remote sensing of the canopy becomes more prevalent, considering the legacy of ungulate herbivory on canopy structure may inform both land management and our understanding of ecological function, such as forest carbon sequestration, maintenance of diverse understory communities, and creation of wildlife habitat Abstract : Using a portable canopy LiDAR system and a former deer enclosure experiment, we show that high deer browsing pressure during stand initiation can have a decades‐long impact on stand and canopy structure. High deer densities led to stands with lower species diversity and tree density, which resulted in canopies that were taller and less dense. As remote sensing of the canopy becomes more prevalent, considering the legacy of ungulate herbivory on canopy structure may inform both land management and our understanding of ecological function, such as forest carbon sequestration, maintenance of diverse understory communities, and creation of wildlife habitat